National Profile of Mercury Use in Costa Rica in light of the Entry into Force of the Minamata Convention - Fernández-Villalobos, Adriana (2017)
Mercury is a metal whose inadequate management can put health and the environment at risk; but in Costa Rica there is no a complete policy that allows the country to establish the controls for its management. Therefore, in 2014, a profile of mercury use was elaborated in Costa Rica in order to identify existing anthropogenic sources, when evaluating the existing capabilities in the country for the management of such metal, in accordance with the implementation of the Minamata Agreement. For its development, extensive bibliographical research and field visits were conducted to all economic activities related to mercury management. According to the analysis, the artisanal mining is considered the riskiest sector since the miners are in constant contact with the metal and manipulate it inadequately. Health facilities, hospitals and dental clinics have limitations due to the lack of legislation and, therefore, weaknesses—such as the lack of training of staff in relation to the risks of mercury and the storage of their wastes in inappropriate places—are identified. On the other hand, cosmetics, biocides, pesticides, and paints are duly regulated with respect to best practices and standards at the international level. Likewise, a vacuum was identified at all stages, including the management of mercury waste at the national level. It is recommended that national plans and strategies be implemented to address the major challenges of mercury management, such as the lack of storage and disposal options.